Gene expression of male pathway genes sox9 and amh during early sex differentiation in a reptile departs from the classical amniote model - Susan Wagner; Sarah L. Whiteley; Meghan Castelli; Hardip R. Patel; Ira W. Deveson; James Blackburn; Clare E. Holleley; Jennifer A. Marshall Graves; Arthur Georges (BMC Genomics, 2023)
Abstract Background Sex determination is the process whereby the bipotential embryonic gonads become committed to differentiate into testes or ovaries. In genetic sex determination (GSD), the sex determining trigger is encoded by a gene on the sex chromosomes, which activates a network of downstream genes; in mammals these include SOX9, AMH and DMRT1 in the male pathway, and FOXL2 in the female pathway. Although mammalian and avian GSD systems have been well studied, few data are available for reptilian GSD systems. Results We conducted an unbiased transcriptome-wide analysis of gonad development throughout differentiation in central bearded dragon (Pogona vitticeps) embryos with GSD. We found that sex differentiation of transcriptomic profiles occurs at a very early stage, before the gonad consolidates as a body distinct from the gonad-kidney complex. The male pathway genes dmrt1 and amh and the female pathway gene foxl2 play a key role in early sex differentiation in P. vitticeps, but the central player of the mammalian male trajectory, sox9, is not differentially expressed in P. vitticeps at the bipotential stage. The most striking difference from GSD systems of other amniotes is the high expression of the male pathway genes amh and sox9 in female gonads during development. We propose that a default male trajectory progresses if not repressed by a W-linked dominant gene that tips the balance of gene expression towards the female trajectory. Further, weighted gene expression correlation network analysis revealed novel candidates for male and female sex differentiation. Conclusion Our data reveal that interpretation of putative mechanisms of GSD in reptiles cannot solely depend on lessons drawn from mammals.